Elmer Gantry [videorecording (DVD)] - Brooks, Richard, 1912-1992; Lancaster, Burt, 1913-1994; Simmons, Jean, 1929-2010; Jagger, Dean, 1903-1991; Jones, Shirley, 1934 March 31-; Lewis, Sinclair, 1885-1951 (Vintage classics, 2001)
One man's fervent pursuit of wealth and power leads him to religion for profit in the evangelist tents of the 1920's Midwestern Corn Belt.